ALMA Lensing Cluster Survey: a strongly lensed multiply imaged dusty system at z ≥ 6. Issue 4 (28th January 2021) - Laporte, N; Zitrin, A; Ellis, R S; Fujimoto, S; Brammer, G; Richard, J; Oguri, M; Caminha, G B; Kohno, K; Yoshimura, Y; Ao, Y; Bauer, F E; et al.
ABSTRACT: We report the discovery of an intrinsically faint, quintuply-imaged, dusty galaxy MACS0600-z6 at a redshift z = 6.07 viewed through the cluster MACSJ0600.1–2008 ( z = 0.46). A ≃ 4σ dust detection is seen at 1.2mm as part of the ALMA Lensing Cluster Survey (ALCS), an on-going ALMA Large programme, and the redshift is secured via [C ii ] 158 μ m emission described in a companion paper. In addition, spectroscopic follow-up with GMOS/Gemini-North shows a break in the galaxy's spectrum, consistent with the Lyman break at that redshift. We use a detailed mass model of the cluster and infer a magnification μ ≳ 30 for the most magnified image of this galaxy, which provides an unprecedented opportunity to probe the physical properties of a sub-luminous galaxy at the end of cosmic reionization. Based on the spectral energy distribution, we infer lensing-corrected stellar and dust masses of 2.9^+11.5_-2.3× 10^9 and 4.8^+4.5_-3.4× 10^6 M_, respectively, a star formation rate of 9.7^+22.0_-6.6 M_ yr^-1, an intrinsic size of 0.54^+0.26_-0.14 kpc, and a luminosity-weighted age of 200 ± 100 Myr. Strikingly, the dust production rate in this relatively young galaxy appears to be larger than that observed for equivalent, lower redshift sources. We discuss if this implies that early supernovae are more efficient dust producers and the consequences for using dust mass as a probe of earlier star formation.